Acoustic processes in RF excited CO2 laser plasma in pulse regime - Wojaczek, Dorota A.; Dobrucki, Andrzej B.; Pliński, Edward F. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Acoustic response to the CO2 laser pulse generation in the arrangement of the slab-waveguide structure is considered. The velocity of an acoustic wave in the carbon dioxide laser gas medium is calculated, and simulation of the wave intensity distribution during the laser plasma pulse developing in the laser cavity is shown. Representation of the laser spectral phenomena in the acoustic signal shape is investigated. The influence of the acoustic wave on the laser frequency operation is considered.
Optica Applicata, Vol. 40, 2010, nr 1, s. 143-153
Keywords: optyka; CO2 laser; molecular laser; gas laser; pulse operation; thermodynamic phenomena